The Effectiveness of Experiential Marketing in Increasing Brand Awareness and Loyalty of MSME Consumers in the Global Market : A Mixed-Methods Approach - Wenny Eka Prasetiawan; Budi Eko Soetjipto (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Micro, Small and Medium Enterprises (MSMEs) face complex challenges in competing in the global market, where innovative marketing strategies such as experiential marketing are believed to increase brand awareness and consumer loyalty. However, its effectiveness is still debated due to inconsistent findings and the lack of holistic studies that combine quantitative-qualitative approaches. This study aims to analyse the influence of the five dimensions of experiential marketing (Schmitt, 1999) on brand awareness and consumer loyalty of global MSMEs, while exploring the challenges of its implementation. A mixed-methods explanatory sequential design method was used, with quantitative SEM analysis (AMOS 28.0) on 250 global consumers and in-depth interviews with 15 MSME players. Results show the feel (β = 0.48, p < 0.001) and relate (β = 0.35, p = 0.002) dimensions have a significant effect on increasing brand awareness, which acts as a full mediator towards loyalty (indirect effect: β = 0.29, p < 0.01). Qualitative findings revealed cultural adaptation and resource allocation as keys to success. This research provides theoretical contributions by extending Schmitt's (1999) model through the integration of brand awareness as a mediator, as well as practical implications in the form of recommendations for glocalisation strategies and the use of AR/VR technology for MSMEs.